Towards sustainability: Photochemical and electrochemical processes applied for environmental protection - Natividad R. (2018)
In the last century, public policy around the globe was mainly focused on economic growth leaving out of this perspective, social concerns and the environment detriment that this merely economic approach was causing. It was until the last quarter of the 20th century that people started to be aware of the growing poverty and of the jeopardy of the planet as a result of human being activities. In consequence, the concept of sustainable development emerged in the United Nations as a call to all countries to integrate economic growth with social needs and environmental protection, in such a way that our activities as earth inhabitants stopped compromising the quality of life and needs satisfaction of future generations.More recently, in 2016, effective 17 sustainable development goals established within the United Nations came officially. The embracement of these goals implies the design and execution of strategies that pursue poverty elimination by also addressing social needs and environmental protection. In this sense, the development of cleaner technologies and more effective sanitation systems is imperative and this has motivated the assessment of new technologies, many of them based on photochemical and electrochemical phenomena. Thus, this special issue aims to present original results regarding relevant aspects of such processes. For this purpose, ten manuscripts have been included.Within the framework of photochemical processes, different issues were addressed ranging from novel photocatalysis approaches, photocatalyst synthesis improvements, emerging contaminant degradation, and photoreactor modeling and simulation.